2018
DOI: 10.3389/fnagi.2018.00324
|View full text |Cite
|
Sign up to set email alerts
|

Corroboration of a Major Role for Herpes Simplex Virus Type 1 in Alzheimer’s Disease

Abstract: Strong evidence has emerged recently for the concept that herpes simplex virus type 1 (HSV1) is a major risk for Alzheimer’s disease (AD). This concept proposes that latent HSV1 in brain of carriers of the type 4 allele of the apolipoprotein E gene (APOE-ε4) is reactivated intermittently by events such as immunosuppression, peripheral infection, and inflammation, the consequent damage accumulating, and culminating eventually in the development of AD. Population data to investigate this epidemiologically, e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(166 citation statements)
references
References 75 publications
9
155
0
2
Order By: Relevance
“…It has been postulated that accumulation of damage from HSV infection and major neuroinflammatory effects can lead to the development of AD, and that apoE4 carriers suffer either greater viral damage or have poorer repair of such damage 54 . Previous studies have demonstrated that ITPKB expression is increased in human AD brains and exacerbates AD pathology in an animal model 64 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that accumulation of damage from HSV infection and major neuroinflammatory effects can lead to the development of AD, and that apoE4 carriers suffer either greater viral damage or have poorer repair of such damage 54 . Previous studies have demonstrated that ITPKB expression is increased in human AD brains and exacerbates AD pathology in an animal model 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the large body of data that amyloid is not causal to AD but rather the result of a protective response (Krstic & Knuesel, ) where amyloid may function as an endogenous antimicrobial peptide (AMP; Moir, Lathe, & Tanzi, ) in response to microbial infection (Itzhaki, ; Dominy et al., ), the current focus on amyloid‐based transgenics may actually be antithetical to AD causality, instead leading to the creation of models of the overexpression of an AMP. Amyloid‐based transgenics also have conceptual limitations when they are used as animal models for non‐amyloid approaches to AD causality like those focused on neuronal network dysfunction, innate immune dysfunction, and chronic inflammation, neurotoxic protein accumulation, cerebrovascular disease, and metabolically‐related diseases that involve mitochondrial dysfunction (Mullane & Williams, ).…”
Section: Beyond Amyloid and Taumentioning
confidence: 99%
“…To this end, we investigated HSV-1 and the Aβ42 peptide, whose aggregation is a major hallmark of AD. Recently, there has been an increasing body of reports suggestive of a correlation between HSV-1 infection and AD, reviewed in 21 . However, evidence of a direct role of HSV-1 in the process of amyloid nucleation and subsequent fibril growth is currently lacking.…”
Section: Hsv-1 Catalyzes Aβ42 Amyloid Aggregation In-vitro and In-vivomentioning
confidence: 99%